2015
DOI: 10.1002/prs.11735
|View full text |Cite
|
Sign up to set email alerts
|

A call to action—next steps for vision 20/20

Abstract: Process safety protects and enhances our individual health, our company's success, and our region's business economy. Companies that handle toxic, flammable, and explosive materials understand the importance of process safety and risk management. So do regulators. So should the community and other stakeholders. Individually, these stakeholders have been working for years to improve process safety performance. Accidents continue to occur. It is time to leverage our resources, knowledge, and skills to all strive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Vision 20/20 was embraced by a variety of organizations. It has been shared within CCPS member companies, as well as with the Institution of Chemical Engineers (IChemE), 2 the American Institute of Chemical Engineers (AIChE), 3 and the Offshore Technology Conference. 4 In 2015, the US Environmental Protection Agency (EPA) indicated support for the stakeholder collaboration called for by Vision 20/20 and indicated that the EPA's report "Actions to Improve Chemical Facility Safety and Security-A Shared Commitment" was very much in alignment with this concept.…”
Section: Impact Of Vision 20/20mentioning
confidence: 99%
“…Vision 20/20 was embraced by a variety of organizations. It has been shared within CCPS member companies, as well as with the Institution of Chemical Engineers (IChemE), 2 the American Institute of Chemical Engineers (AIChE), 3 and the Offshore Technology Conference. 4 In 2015, the US Environmental Protection Agency (EPA) indicated support for the stakeholder collaboration called for by Vision 20/20 and indicated that the EPA's report "Actions to Improve Chemical Facility Safety and Security-A Shared Commitment" was very much in alignment with this concept.…”
Section: Impact Of Vision 20/20mentioning
confidence: 99%
“…The emphasis in the CCPS Vision 20/20 tenet, Disciplined Adherence to Standards, is creating and following standards for existing equipment . Normally when Vision 20/20 is discussed, standards for existing equipment is briefly mentioned, but not thoroughly described.…”
Section: Introductionmentioning
confidence: 99%